Leptin Increases Blood Pressure and Markers of Endothelial Activation during Pregnancy in Rats. (19th September 2013) - Ibrahim, Hisham Saleh; Omar, Effat; Froemming, Gabrielle Ruth Anisah; Singh, Harbindar Jeet
Abstract : Raised leptin levels have been reported in the placentae and serum of women with elevated blood pressure and proteinuria during pregnancy. The role of leptin in this however remains unknown. This study investigates the effect of leptin administration on systolic blood pressure (SBP) and proteinuria and serum markers of endothelial activation during pregnancy in Sprague Dawley rats . From day 1 of pregnancy, 24 rats were randomised into those given either saline (group 1) or leptin at 60 or 120 μ g/kg/body weight/day (groups 2 and 3 resp.). SBP was measured every 5 days and 24-h urinary protein was measured at days 0 and 20 of pregnancy. Animals were euthanised on day 20 of pregnancy, and serum was collected for estimation of E-selectin and ICAM-1. Compared to group 1, SBP during the latter part of the pregnancy was significantly higher in the leptin-treated group (P < 0.01 ). Urinary protein excretion, serum E-selectin, and ICAM-1 were significantly higher in leptin-treated rats (P < 0.05 ). It seems that leptin administration to normotensive Sprague Dawley rats during pregnancy significantly increases SBP, urinary protein excretion, and markers of endothelial activation. However, further studies are required to examine the underlying mechanism responsible for this and its relevance to preeclampsia in humans.